2000
DOI: 10.1053/jpro.2000.18551
|View full text |Cite
|
Sign up to set email alerts
|

Effect of denture cleansers, surface finish, and temperature on Molloplast B resilient liner color, hardness, and texture

Abstract: After silicone resilient denture liner treatment with certain perborate-containing denture cleansers, a greater amount of components could leach from the liner leading to a loss of color if the liner surface is rough.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 10 publications
1
23
0
3
Order By: Relevance
“…Reline materials can be colonized by microorganisms due to their porous and micro-retentive surface characteristics [22][23][24] . The results of in vitro studies revealed that smoother surfaces retain fewer cells whereas rough surfaces promote the adhesion of microorganisms [25][26][27][28] . The influence of various denture cleansers on the surfaces of denture base and soft reline resins have been reported by several studies whereas there are only a limited number of studies which have evaluated the effect of denture cleansers on the surface roughness of hard permanent reline resins [26][27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
“…Reline materials can be colonized by microorganisms due to their porous and micro-retentive surface characteristics [22][23][24] . The results of in vitro studies revealed that smoother surfaces retain fewer cells whereas rough surfaces promote the adhesion of microorganisms [25][26][27][28] . The influence of various denture cleansers on the surfaces of denture base and soft reline resins have been reported by several studies whereas there are only a limited number of studies which have evaluated the effect of denture cleansers on the surface roughness of hard permanent reline resins [26][27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate cleaning by the patient leads to microbial growth on liner surface and denture stomatitis. Inadequate cleaning could also contribute to deterioration of desirable liner properties (14).…”
Section: Introductionmentioning
confidence: 99%
“…7,13,17 Usumez at al. 13 tested the tensile bond strength of the adhesion of commercially available siliconebased soft denture liners to standblasted and lased acrylic resins.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate cleaning could also contribute to deterioration of desirable liner properties such as resilience, texture, roughness and color. 7 Common daily methods for cleaning dentures include brushing and use of immersion cleaners. 8,9 The solutions used for denture cleaning can be divided according to their chemical compositions or mode of action: alkaline peroxide, alkaline hypochlorites, acids, disinfectants, mouth rinses for dentures, and enzymes.…”
Section: Introductionmentioning
confidence: 99%